The professorship of primary education before the ITC: reality and challenges - Fº Javier Trigueros Cano; Raquel Sánchez Ibáñez; Mª Isabel Vera Muñoz (Revista Electrónica Interuniversitaria de Formación del Profesorado)
From diverse studies of case an approximation appears to the utilization on the part of the professorship of Infantile and Primary Education in diverse centers of education of the Comunidad Autónoma de la Región de Murcia of the technologies of the information and the communication. The results indicate that in spite of the high valuation for the professorship of the ICT like didactic tool in the classroom and the progressive endowment of technological resources in the schools in the last ten years, the utilization of the ICT for the professorship still is scanty. The principal motives are the difficulties for the formation in the use of the new technologies and the excessive time that carries the preparation of didactic materials.